The relationship between theory and power in platonic politea - Costa, Erika Bataglia da (Argumentos - Revista de Filosofia, 2010)
Faced with the deterioration of democratic politics, Plato sets out to translate policy into tékhn. This is the State subject to the rule of theoria that reveals the foundations of the cosmos, and thus the very possibility of society and state. With that guarantee the bonds of a statesman and an absolute axial epistemic able to make exclusive to an elite spiritual practice of power. Thus, it satisfied the requirement of field competent and universally established that characterizes the notion of tékhne. However, in conjunction with restriction on the extent of political activity, there is also a deepening of their assumptions whose explanation depends on a rise dialectical philosophy inspired by eroticism, understood as the sum of avoidance which makes possible the noetic intuition.